Group of teenage girls working on projects in a forest setting - Unknown:::Creator::::::::::::
Photograph shows a group of teenage girls working on projects at tables in a forest setting. The table in the foreground shows one girl using a table vice while two others look on. That table has many different sized pieces of wood on it which appears to have been gathered from the forest. There are tents in the background. The location is probably the YWCA's Camp Ayun Mapu in Big Basin, California